LGG-52. DUAL INHIBITION OF mTORC1/C2 AND MEK PATHWAY IS SYNERGISTIC IN MULTIPLE HUMAN MODELS OF PEDIATRIC LOW-GRADE GLIOMA INCLUDING A NOVEL PATIENT-DERIVED NF1 PILOCYTIC ASTROCYTOMA CELL LINE. Issue 2 (22nd June 2018) - Arnold, Antje; Yuan, Ming; Rodriguez, Fausto; Eberhart, Charles; Raabe, Eric
Abstract: Pediatric low-grade glioma (PLGG) is the most common brain tumor of childhood. We and others have identified mTORC and MEK-activation in PLGG. The dual mTORC1/2-inhibitor, TAK228, and the FDA approved MEK-inhibitor, trametinib, are promising candidates for targeted PLGG therapy. We treated five different patient-derived PLGG cell models with TAK228 and/or trametinib: JHH_NF1_PA1 (NF1 mutation), BT66_SV40/hTERT (BRAF:KIAA1549 fusion), BT40 (BRAFV600E) Res186 (PTEN deletion) and Res259 (PDGFRα amplification and CDKN2A deletion). In vitro, treatment with TAK228 or trametinib reduces cell proliferation in a dose and time depended manner investigated via MTS-assay. Both drugs exert a synergistic effect at 5-20nM in JHH_NF1_PA1, Res186, and Res259 cells. BT66_SV40/hTERT cells have a 70% reduction in cell growth with 10nM TAK228 (p<0.001 by ANOVA) but not in combination with trametinib. In all cell lines trametinib treatment leads to a pERK inactivation at low nM levels. TAK228 treatment leads to an inactivation of mTORC1 and mTORC2. Apoptosis induction was verified through cleaved PARP via western blot and CC-3 via immunocytochemistry. The combination of TAK228 and trametinib increased apoptosis by up to 127% (p<0.001) in Res186, Res259, and JHH_NF1_PA1 cells. In vivo, BT40 tumor cells were investigated with both agents in immunodeficient mice. In combination TAK228 and trametinib decreased significantly BT40 PLGG xenograft tumor growth compared to vehicle or either agent alone, (p<0.01 by ANOVA). Our results show that PLGG-derived cell lines are sensitive to TAK228 and trametinib treatment. The ongoing in vivo experimentation will provide a pre-clinical rationale for combination therapy of these agents in aggressive PLGG.